KETERKAITAN ANTIGEN NS1 INFEKSI VIRUS DENGUE DENGAN SEROTIPE VIRUS DENGUE - Roudhotul Ismaillya Noor; Aryati Aryati; Puspa Wardhani (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Dengue virus infection (DVI) currently is detected by using dengue virus NS1 antigen (NS1 Ag). The sensitivity of NS1 Ag is 27.8%–93.4%,but recent study of Kumarasamy the sensitivity of NS1 Ag is better than the virus isolation and polymerase chain reaction (PCR). This studyis focussed on the evaluation of the validity of Panbio Dengue Early Rapid for the diagnosis of DVI and the NS1 Ag sensitivity associated withdengue virus serotypes. The sera was obtained from 65 DVI patients which diagnosed by the clinicians. The resulted diagnosis was foundby serology tests (positive IgM/IgG antidengue/NS1 Ag ELISA) and 1997 WHO criteria as the gold standard, and which also found 35 nonDVI patients (typhoid fever, HAV, malaria, UTI, tuberculosis and bronchopneumonia). The samples were examined by Panbio Dengue EarlyRapid. PCR was performed on each positive serological test result to determine the dengue virus serotypes. The sensitivity and specificity ofPanbio Dengue Early Rapid was 49.2% and 100%. The PCR results of 65 sera showed positive PCR in 49.2% (positive NS1 Ag was 62.5%).Meanwhile, and negative PCR in 50.8% (positive NS1 Ag was 36.4%). The predominance of serotypes (positive NS1 Ag) were DEN-3 (37.5%),DEN-4 (28.1%), DEN-1 (21.9%) and DEN-2 (12.5%). The Panbio Dengue Early Rapid can be used as early detection of DVI, although itshould be used in conjunction with other dengue serological tests as well. Unfortunately there is still not enough evidence about the NS1 Agsensitivity associated with the dengue virus serotypes.